Effect of Electric Pulse Treatment on the Interfacial Properties of Copper/304 Stainless Steel Composite Thin Strips Fabricated by Roll Bonding - Zefeng Wang; Xiaomiao Niu; Ming Wang; Yu Yang; Dongping He; Wangzhe Du (Metals)
Annealing is a commonly used post-processing method for composite thin strips but suffers from drawbacks such as long processing time, high energy consumption, and susceptibility to oxidation. Replacing annealing with electric pulse treatment (EPT) can address these issues. In this study, a specially designed fixture was used to investigate the effects of pulsed current on the bonding strength of T2 copper (Cu)/304 stainless steel (SS) composite thin strips. The initial strip, with a 50% reduction rate, was prepared using a two-high mill, resulting in a Cu/SS composite strip with a thickness of 0.245 mm. Pulsed current treatment was applied with peak temperatures ranging from 350 °C to 600 °C. The results showed that EPT significantly improved the bonding strength. A pulsed current of 55 A resulted in the highest average peel strength of 10.66 ± 0.93 N/mm, with a maximum Fe content on the Cu side of 7.39 ± 0.84%, while a pulsed current of 65 A resulted in the highest Cu content on the SS side, reaching 57.54 ± 2.06%. This study demonstrates that EPT effectively controls the deformation behavior and interface state of composite strips, producing Cu/SS composite thin strips with high bonding strength.